Influence of copper on the instability and corrosiveness of palm biodiesel and its blends: An assessment on biodiesel sustainability. (10th January 2018) - Fazal, M.A.; Suhaila, N.R.; Haseeb, A.S.M.A.; Rubaiee, Saeed; Al-Zahrani, A.
Abstract: Biodiesel is comparatively more corrosive than petroleum diesel; therefore, the issue of sustainability has become a major concern. Biodiesel is auto-oxidative in nature; thus, its fuel properties could be changed. The present study aims to investigate the sustainability of biodiesel and its different blends with diesel in terms of instability and corrosiveness upon exposure to copper. The investigated fuels are diesel, 20% biodiesel in diesel, 50% biodiesel in diesel, and pure biodiesel. Immersion tests in the absence and presence of 100 ppm tert-butylamine or butylated hydroxyanisole additive were conducted at temperatures of 25 °C–27 °C for 600 and 1200 h. At the end of the tests, corrosion of copper was examined by weight loss measurement and changes on the metal surface. Metal surfaces were characterized by scanning electron microscopy, energy dispersive spectroscopy, X-ray diffraction, and atomic force microscopy. Fuel was analyzed by gas chromatography–mass spectroscopy, and its properties were investigated by density meter and Rancimat method. Results show that corrosion rate of copper in biodiesel or its high percentage of blends rises with the increase in immersion time. Corrosion rate of copper in diesel and 20% diesel–biodiesel blends are similar and do not significantly change with immersion time. To improve sustainability, BHA is found to be effective in reducing biodiesel oxidation, whereas TBA reduces the metal surface degradation. Highlights: Corrosiveness of B20 (20% biodiesel and 80% diesel) and diesel seems to be similar. Biodiesel is compositionally changed slightly upon exposure of copper. Oxidation stability of palm biodiesel upon exposure to copper was found to be very poor.